The Innovative Strategies for Integrating Technology into Agricultural TVET Programs in South African - Ramongwane Daniel Sephokgole (Studies in Learning and Teaching, 2026)
Integrating technology into Technical and Vocational Education and Training (TVET) is a smart move to align agricultural education with the demands of the global economy. This mixed-methods approach exposes infrastructure and training inadequacies that impede market-oriented teaching by comparing the usage of modern agricultural equipment and basic classroom ICT in TVET colleges. Data was gathered from 482 National Accredited Technical Education Diploma (NATED) and National Certificate of Vocational NC(V) students in three chosen TVET colleges using a questionnaire and observation schedule. Pearson chi-square tests and descriptive analysis showed that most variables had extremely significant associations (P<0.05). The findings indicated that students view technology as a suitable tool to utilize, but they are hampered by poor connectivity and a shortage of technical learning tools. Technological tools should be made available to TVET colleges to facilitate digital training in their programs. The modern existing technologies can be integrated to enhance theoretical learning, professional skills, and the noticeable "digital divide." Therefore, TVET colleges ought to invest in robust ICT infrastructure and specialized professional development. To determine how precision agricultural technologies affect TVET students' employment after graduation, more long-term research is advised.